Zwitterionic materials for aqueous Zn-based energy storage devices: Current developments and perspective - Huaming Yu; Zhongqian He; Dongping Chen; Peidong Liu; Hanwei He; Liangliang Jiang; Yuejiao Chen; Libao Chen (Energy Reviews)
Aqueous Zn-based energy storage (AZES) devices are promising candidates for large-scale energy storage systems. Nevertheless, AZES devices still face some critical bottlenecks and challenges, including poor chemical stability of Zn anode and a narrow operating voltage window of aqueous electrolyte. Zwitterions are typically organic salts in which cations and anions are covalently bonded. Zwitterionic materials have garnered considerable research attention in the field of electrochemical energy storage due to their solubility in polar solvents, strong hydration ability, and dipole formation for the transfer of carriers. Zwitterionic materials have been shown to achieve excellent effects on addressing the issues in AZES devices, yet the explorations with limited understanding of the functional mechanism and design basis of the zwitterionic materials. Accordingly, this review discusses the unique structure and characteristics of zwitterionic materials and summaries the applications and mechanisms of zwitterionic materials in AZES devices. Finally, the challenges and perspectives of zwitterionic materials working in the AZES devices optimization are offered for future research.